Use of water test to assess the sperm membrane functional integrity in cryopreserved bull semen - Nava Trujillo, Héctor; Quintero Moreno, Armando; Osorio Meléndez, Carla; Rubio Guillén, Jorge; Carrillo Fernández, Freygelinne; Finol Parra, Geovanny (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
The hypoosmotic swelling test (HOST) has been used to asses the sperm membrane functional integrity in bulls. However, for human, goat and dog semen, the water test (WT) has been proposed as a replacement to HOST, because WT uses distilled water and only five minutes of incubation. The aim of the present study was to compare the HOST and the WT to assess the sperm membrane functional integrity of cryopreserved bull semen. The percentage of sperm with swelling tail was higher in WT (54.85 Ó 13.63%, P